Pocket-cubes, bringing multidimensional data views to mobile platforms - Ribeiro, Jorge (2014)
From simple entertainment gadgets to real world based applications, a little bit of everything is in a mobile platform. Thus, it’s not a surprise that enterprise managers, decision makers or business analytics use it also to support their most regular daily business activities. Following the same fast adoption path of other applications, their analytical needs quickly appeared in their horizon as one of the most useful applications that they could bring in their “pockets”. The data structures of such applications are very large to be received by mobile platforms. Data cubes still are quite out from currently mobile platforms’ data manipulation boundaries. However, a lot of efforts were developed during the last few years to provide smaller hyper cubes with the same exploitation potentialities, requiring less computational resources as disk storage and processing time, appealing to better data compression techniques or multidimensional views selection. In this paper we present the most usual techniques for compressing and processing data cubes. In order to support such approach we designed and developed the Pocket Cubes system, an application especially oriented to prepare data cubes to be used on mobile platforms.